Non-compliance factors of the waste control protocol based on the COSO ERM 2017 methodology in the production process of stone coal - Alfaro Oliva, Joselito Emanuel (2020)
In this research work of quantitative approach, the general objective was to determine the                     noncompliance                     factors of the waste control protocol based on the methodology proposed by the                     Committee of Sponsoring Organizations of the Treadway. This methodology was applied in a                     company located in the northern mountains of Peru and dedicated to the extraction and processing                     of stone coal, considering that control activities have an impact on the eficiency and                     efiectiveness of business production. This research was carried out in the storage area, because                     in the coal stacking stage the problem of waste occurs, something common in most coal mining                     companies and that has a negative impact on its economy and the sector. A holistic evaluation                     was carried out, considering the collaborators of the storage area. In conclusion, it was found                     that: the inadequate supervision of policies, low capacity to respond to risks, lack of speedy                     attention to risks, low inspection of risks and socialization of protocols; and the low level of                     implementation, compliance and verification of policies, are the main factors.